An adaptive character skinning algorithm based on the property of real skin. (13th December 2018) - Wu, Huayue
Abstract: Current methods for character skinning usually include weight binding and automatic skinning such as linear blend skinning (LBS) and dual quaternion skinning (DQS). However, weight binding is a tedious work; LBS and DQS suffer from their own artifacts. The latest research studies could produce better effect; however, their application in real‐time situations is limited due to the requirement of a large amount of first‐phase preparations and huge computation. This paper proposed a new approach that uses the property of real skin for skinning, which could produce a more natural and realistic effect and could greatly promote skinning efficiency. An optimized mathematical model is also used to compute mesh deformation; therefore, the render speed is greatly promoted and the effect of bulging muscles and fat could also be simulated. Abstract : This paper uses a mapped ellipsoid to generate skinning region and real skin properties to establish the skinning parametric equations, in order to produce a much realistic skinning effect, faster rendering speed, and muscle and fat bulging effect. Moreover, the usage of the property of real skin for skinning could greatly promote skinning efficiency.